Effectiveness of the Corruption Crime Judge Selection Process in Preventing Corruption in Indonesian Judicial Institutions - Maulana, Afini (Innovative: Journal Of Social Science Research, 2024)
The purpose of this research is to determine how well the criteria used to choose judges for the Corruption Court work to keep corrupt officials out of the courtroom. This study employs normative legal research methods to analyze relevant laws and regulations, such as Law No. 46 of 2009 and Supreme Court Regulation No. 2 of 2019, which deal with the selection of ad hoc judges. The goal is to determine if the selection process has been successful in ensuring that judges are honest. The research found that judges serving on the Corruption Court are susceptible to corrupt conduct due to external influences and gaps in post-selection monitoring, notwithstanding the rigorous screening process. This is made worse by factors including lax internal oversight mechanisms, a lack of stringent punishments, and economic and political pressures. To guarantee a more effective supervision and selection system, comprehensive changes are required, such as enhancing monitoring, making punishment enforcement more transparent, and improving judges' welfare.